Pupation site preference selection in Drosophila jambulina. Issue 4 (4th July 2019) - Ramniwas, Seema; Kumar, Girish
Abstract : Larvae of three latitudinally different populations of Drosophila jambulina belonging to the montium subgroup were tested for pupation site preference in relation to temperature. At 30 °C, larvae preferred to pupate on food whereas at 21 °C pupation occurred on the cotton. Genetic basis of larval pupation behavior was studied by conducting reciprocal crosses for 30 generations on food-selected and on cotton-selected pupae. Results from genetic analysis between food-selected and cotton-selected strains indicated a single gene responsible for the pupation site preference, with F1 progeny pupated on cotton and F2 (F1 × F1 ) larvae pupated on both food as well as on cotton. Although we found no change in morphological traits in food vs cotton selected populations, significantly different growth rate (body weight) between the two strains was observed. These results suggest that pupation site preferences can affect life-history traits in D. jambulina.